Influences of environmental and operational factors on dark fermentative hydrogen production: a review - Mohammadi, P.; Ibrahim, S.; Annuar, M.S.M.; Ghafari, S.; Vikineswary, S.; Zinatizadeh, A.A. (2012)
Hydrogen (H2) is one of renewable energy sources known for its non-polluting and environmentally friendly nature, as its end combustion product is water (H2O). The biological production of H2 is a less energy intensive alternative where processes can be operated at ambient temperature and pressure. Dark fermentation by bacterial biomass is one of multitude of approaches to produce hydrogen which is known as the cleanest renewable energy and is thus receiving increasing attention worldwide. The present study briefly reviews the biohydrogen production process with special attention on the effects of several environmental and operational factors towards the process. Factors such as organic loading rate, hydraulic retention time, temperature, and pH studied in published reports were compared and their influences are discussed in this work. This review highlights the variations in examined operating ranges for the factors as well as their reported optimum values. Divergent values observed for the environmental/operational factors merit further exploration in this field. Â© 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.